Pengaruh Konsentrasi dan Jenis Gula Terhadap Minuman Fermentasi Kulit Nanas (Tepache) - Muhamad Mubiar Ramadana; Ingrie Laila; Mukhtar Ghulam Halim; Najmi Azalia Ubaedilah; Ateng Supriyatna (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Pineapples are often consumed by humans and produce waste from pineapple skin, but the content of pineapple skin has a water content of 81.72%, crude fiber 17.53%, carbohydrates 4.41%, protein and reducing sugar both have the same content of 13.65%. Usually Mexican people make pineapple skin as a fermented probiotic drink or also called tepache. With the fermentation process in this probiotic drink, of course there is the effectiveness of the Lactobacillus casei microbe which has the ability to inhibit pathogenic bacteria that have the potential in making tepache which is utilized from pineapple skin against sugar concentration. Using the Experimental research method is a systematic, careful, and logical study to control a condition. From making pineapple tepache will produce different tastes, colors, textures and aromas. The less sugar concentration, the more sour it tastes and vice versa. the more sugar concentration, the sweeter it tastes. This is because there is a percentage of lactic acid which will lower the low pH value at the sugar concentration in it.